Efektivitas Insektisida Metomil 40% Terhadap Serangan Ulat Grayak (Spodoptera Exigua Humber) pada Tanaman Bawang Merah (Allium Cepa L.) di Desa Songan Kintamani Bangli - HENDRA, I MADE REDI DWIJAYA; SUMIARTHA, I KETUT; SUSILA, I WAYAN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.7, No.2, April 2018, 2018)
The Effectiveness of Metomyl Insecticide 40% to Armyworm (Spodoptera exigua Hubner) On Red Onion Plant (Allium cepa L.) in Songan Village District of Kintamani Bangli Regency The Research of Metomyl Insecticide 40% to damage caused by armyworm (Spodoptera exigua Hubner) On Red Onion Plant (Allium cepa L.) in Songan Village District of Kintamani Bangli Regency was conducted in order to determine the percentage of damage of armyworm (Spodoptera exigua) and the relationship between the pareentage of damage and production after treated by metomil insecticide 40%. This onion tuber harvest after treatment with insecticide with 40% active metomyl.this research was done from 2016, November until 2017 January. Randomized block design was used in this studay with 5 treatments and replicated 5 times. The results showed that the perceutage of demage caused by Spodoptera exigua on onion plant treated by metomiyl insecticide 40% were significant different compare to control. The highest percertage of damage was found in control 13.5% and the lowest percentage of damage was found in treated consentration of 2,00 g/l, was 1,99%, both was observed in 49 days after transplanting, the production of wet tuber in average was found 1,3 kg in treatment of 2g/l and 1,1kg in countred, the production was calculated by avrage of 10 plants. The relationship between percentage of damage and production are very weak to strong unsignificant and reversely propotional.